1961
DOI: 10.1126/science.133.3457.1016
|View full text |Cite
|
Sign up to set email alerts
|

Critical Period in the Social Development of Dogs

Abstract: Litters of puppies were isolated, with the bitch, in fenced acre fields from 2 to 14 weeks of age. They were removed indoors at different ages, played with for a week, and returned to the field. The pups manifested an increasing tendency to withdraw from human beings after 5 weeks of age and unless socialization occurred before 14 weeks of age, withdrawal reactions from humans became so intense that normal relationships could not thereafter be established

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(126 citation statements)
references
References 2 publications
1
118
0
2
Order By: Relevance
“…AC is good for command training, but too late for socialization. Previous studies have indicated that a dog's experience during the socialization period has a strong influence on future behavioral development [1,6,17,19]. Scott and Fuller defined the period of socialization as between 3 and 12 weeks from the results of a study on complete isolation in laboratory animals [17].…”
Section: Discussionmentioning
confidence: 99%
“…AC is good for command training, but too late for socialization. Previous studies have indicated that a dog's experience during the socialization period has a strong influence on future behavioral development [1,6,17,19]. Scott and Fuller defined the period of socialization as between 3 and 12 weeks from the results of a study on complete isolation in laboratory animals [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although we should point out that, if early human contact is provided, many individuals of even a wild species can be socialized to humans, dogs' long evolutionary history places them in a unique position. In contrast to wolves, whose socialization to humans has to begin before day 10 (eye opening) (Klinghammer & Goodmann, 1987;Frank, Frank, Hasselbach, & Littleton, 1989), the time window for socialization in dogs (Scott & Fuller, 1965), probably closes at around 12 weeks (Freedman, King, & Elliot, 1961). Social attraction to humans develops even after 20-minute encounters twice a week, or daily eye contact with humans (Scott & Fuller, 1965).…”
Section: Naturalistic Socialization With Humansmentioning
confidence: 99%
“…mounting) first emerge during the socialization period that begins at 3 weeks and ends at approximately 12 weeks of age (Freedman et al 1961;Scott & Fuller 1965). During this time, puppies learn social skills and form bonds with other dogs (Lindsay 2000), and play-partner preferences may begin to form.…”
mentioning
confidence: 99%